The identification of spatial dependence in the analysis of regional economic development - join-count test application - Michal Bernard Pietrzak; Justyna Wilk; Tomasz Kossowski; Roger Bivand (Institute of Economic Research (IER), 2013)
The content of the article is focused on the problem of spatial dependence identification, referring to the analysis of regional economic development. Economic development, as an economic category, represents a very extensive concept. Within its framework the following problems should be considered: the influence of institutions performing social services, environmental conditions of residence and the overall complex of general economic phenomena. The correct measurement of economic development requires the selection of adequate diagnostic variables as well as the construction of the taxonomic measure of development. The implementation of taxonomic measure of development allows for the division of regions into homogenous classes, however, reduces the possibility of statistical tests usage for quantitative data, which decide about the occurrence of spatial dependence. The objective of the article is to identify spatial dependence of regions covered by classes characterized by the defined economic development level having applied the join-count test. This test allows detecting the spatial autocorrelation for quantitative data. The test application allows detecting whether the regions, within the framework of each specified class, are grouped based on the existing spatial dependence and create clusters featuring similar economic development level.
Keywords: J11; O11; O15; R11; R23; 330; economic situation; internal migration; synthetic measure; ratio analysis; classification